Reversible DC Electric Field Modification of Optical Properties of CdTe Nanocrystals - Ince, Rabia; Alper, Melda Patan; Yukselici, Mehmet Hikmet (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Modifiable nonlinear optical properties have the potential for innovative device applications. Quantum dot systems have an energy level system that is modified under external electric fields, modifying their optical properties. The matrix surrounding the quantum dot systems influences this optical modification. In this work absorption spectra of cadmium telluride quantum dot systems in solution and solid glassmatrixeswere studied under increasing appliedD.C electric fields between 0.25 and 5 kV/cm. Quantum dot systems in both solid glass and liquid solution matrixes gave rise to electro-optic effects, which modified their optical properties (absorption spectra, bandgap energy and refractive index). The effect is reversible, so that removal of the electric field returns the original electro absorption spectra. This work showed all nanoparticle samples except one displayed a linear decrease of band gap energy with electric field; this amounted to equivalent changes in quantum dot radii of 0.02 nm per kV in glass matrixes and about 0.03 nm per kV for solution matrixes. Evidence of improved mono-dispersity was also observed.
Keywords: QUANTUM; ELECTROABSORPTION; SIZE; NANOPARTICLES; ABSORPTION; ENERGY; Science & Technology - Other Topics; Materials Science; Physics